The Reflections of the “Stop Climate Change Digital Game” on Primary School Students' Learning about Climate Change - Sahin Idil; Orkun Kocak (Journal of Education in Science, Environment and Health)
Climate change and its effects are impacting our world more and more with each passing day. For this reason, we must ensure that our children, as the society of the future, grow up as individuals with high environmental awareness, being aware of climate change and its effects. The aim of this study is to inform students about the subject of climate change and to educate them as individuals with climate change literacy. In this context, a digital game about climate change and its effects was developed for primary school students. A qualitative research method and techniques were adapted in this research. Interview, observation, and document analysis techniques were used to ensure variety in data acquisition in the research. The study was conducted in the 2022 spring semester during the science courses. It was conducted at an urban primary school in Ankara. 22 fourth grade students were participated as control group and 23 fourth grade students were participated as treatment group in the study. It was determined that the students enjoyed this game, called Stop Climate Change; they had fun and simultaneously learned about concepts related to climate change.